2013
DOI: 10.1002/stem.1483
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells inhibit cutaneous radiation-induced fibrosis by suppressing chronic inflammation

Abstract: Exposure to ionizing radiation (IR) can result in the development of cutaneous fibrosis, for which few therapeutic options exist. We tested the hypothesis that bone marrowderived mesenchymal stem cells (BMSC) would favorably alter the progression of IR-induced fibrosis. We found that a systemic infusion of BMSC from syngeneic or allogeneic donors reduced skin contracture, thickening, and collagen deposition in a murine model. Transcriptional profiling with a fibrosis-targeted assay demonstrated increased expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
99
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 52 publications
1
99
0
1
Order By: Relevance
“…MSCs are multipotent progenitor cells that have multi-lineage differentiation potential and recently identified anti-inflammatory and immunomodulatory properties that have been applied in numerous current preclinical and clinical studies [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Mesenchymal Stromal/stem Cells Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs are multipotent progenitor cells that have multi-lineage differentiation potential and recently identified anti-inflammatory and immunomodulatory properties that have been applied in numerous current preclinical and clinical studies [55][56][57][58][59][60][61][62][63][64][65][66][67][68][69][70].…”
Section: Mesenchymal Stromal/stem Cells Therapymentioning
confidence: 99%
“…MSCs have been used in the repair of radiation-induced skin injuries where they were administered systemically and lead to decreased radiation-induced skin fibrosis through enhancing the secretion of IL-10 and increasing the infiltration of antiinflammatory regulatory CD163(+) macrophages, decreasing the secretion of IL-1 beta and the numbers of infiltrated pro-inflammatory CD80(+) macrophages [69]. It was suggested that the autologous grafting of MSCs is more efficient than the allogenic grafting in cutaneous radiation syndrome [83].…”
Section: Skin Repair Application After Radiation Exposurementioning
confidence: 99%
“…More recent studies of wound healing have focused on mesenchymal stem cells (MSCs)-nonhematopoietic, adherent fibroblast-like cells with intrinsic capacity for self-renewal and differentiation-as a possible cell population within the bone marrow that might contribute to cutaneous repair, particularly in radiation burns [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Manuscripts covered many advances in understanding the fundamental mechanisms that control stem and progenitor cell fate, and advances in working toward treating all tissues, from the lower extremities to the brain. Exciting basic and translational research was reported in using stem cells to treat osteoporosis [11], spinal cord injuries [12,13], radiation-induced fibrosis [14], glaucoma [15], globoid cell leukodystrophy [16], stroke [17], and Huntington's disease [18], to name just a few. It has truly been an exciting year, as we watch the stem cell field explode.…”
mentioning
confidence: 99%